2021
DOI: 10.1115/1.4049535
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Surface Defect Detection Using Deep Learning: A Review

Abstract: Automatically detecting surface defects from images is an essential capability in manufacturing applications. Traditional image processing techniques were useful in solving a specific class of problems. However, these techniques were unable to handle noise, variations in lighting conditions, and background with complex textures. Increasingly deep learning is being explored to automate defect detection. This survey paper presents three different ways of classifying various efforts. These are based on defect det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(50 citation statements)
references
References 57 publications
0
29
0
2
Order By: Relevance
“…Some studies have a different focus from our research. The article [81] investigates supervised and semi-supervised deep learning algorithms. As for the unsupervised aspect, more attention is paid to the different network architectures used by different types of algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…Some studies have a different focus from our research. The article [81] investigates supervised and semi-supervised deep learning algorithms. As for the unsupervised aspect, more attention is paid to the different network architectures used by different types of algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…ese high-resolution scanners are very expensive, and because of the high resolution they use, the scanning process of an entire wafer takes an inexcusably long amount of time [6].…”
Section: Introductionmentioning
confidence: 99%
“…He et al developed a regression-and classification-based framework for generic industrial defect detection [23]. Bhatt et al summarized the recent progress in surface defect detection using DL techniques and concluded that DL has been widely explored for use in the automation of defect detection [24]. However, the concurrent identification approach has limitations in multiple defect detection owing to the need for labeled defect data for training; some defects may not be detected when they are rare or unlabeled and when data on these defects are insufficient.…”
Section: Introductionmentioning
confidence: 99%